The Role of Parents in Student Learning at SMA Takhasus Al-Qur’an Bulakwaru Tarub, Based on Pesantren (Islamic Boarding School) - Mastuti, Eli; Nur Rahma, Elyfa; Nurul Inayah, Isnaeni; Pradita, Ristanti; Khotami, Femi; Amin Fadhil, Choirul; Saidin (CV Kalimasada Group, 2025)
Purpose - This research aims to examine the role of parents in the learning process at the Islamic boarding school-based Takhasus Al Quran Bulakwaru Tarub High School. In the context of Islamic boarding school-based education, parents play an important role in supporting students' academic success and character development Design/Methodology/Approach - The method used in this research is descriptive qualitative, with data collection through interviews, observation, and documentation studies. Findings - The research results show that parents' involvement in their children's education includes moral support, facilitation of learning needs, and good communication between school and family. Apart from that, parents also play a role in instilling religious and ethical values in their children, which are in line with the educational goals of Takhasus Al Quran High School. This research concludes that synergy between parents and educational institutions is very important in improving the quality of learning and appreciation of the teachings of the Quran among students. Originality/Value The findings are expected to provide insight for parents, educators, and Islamic boarding school managers in formulating more effective educational strategies, especially in strengthening collaboration between families and Islamic boarding school-based educational institutions.